Discovery of Lipoxygenase-Like Materials for Inducing Ferroptosis - Xie, Qianqian; Li, Wenjie; Chen, Changzhi; Yang, Qing; Jiang, Jie; Cai, Xiaoming; Li, Ruibin (ACS nano, 2024)
Recent research has highlighted the pivotal role of lipoxygenases in modulating ferroptosis and immune responses by catalyzing the generation of lipid peroxides. However, the limitations associated with protein enzymes, such as poor stability, low bioavailability, and high production costs, have motivated researchers to explore biomimetic materials with lipoxygenase-like activity. Here, we report the discovery of lipoxygenase-like two-dimensional (2D) MoS2nanosheets capable of catalyzing lipid peroxidation and inducing ferroptosis. The resulting catalytic products were successfully identified using mass spectrometry and a luminescent substrate. Unlike native lipoxygenases, MoS2 nanosheets exhibited exceptional catalytic activity at extreme pH, high temperature, high ionic strength, and organic solvent conditions. Structure-activity relationship analysis indicates that sulfur atomic vacancy sites on MoS2 nanosheets are responsible for their catalytic activity. Furthermore, the lipoxygenase-like activity of MoS2 nanosheets was demonstrated within mammalian cells and animal tissues, inducing distinctive ferroptotic cell death. In summary, this research introduces an alternative to lipoxygenase to regulate lipid peroxidation in cells, offering a promising avenue for ferroptosis induction.
Keywords: Humans; Catalysis; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; nanocatalyst; molybden; disulfidy; peroxidace lipidů; Lipoxygenase; Nanostructures; lidé; zvířata; myši; lipoxygenasa; nanostruktury; Mice; lipid peroxidation; biomimetické materiály; Disulfides; Molybdenum; Ferroptosis; ferroptóza; ferroptosis; Animals; Biomimetic Materials; nanobiology; katalýza; Lipid Peroxidation; nano-bio interaction